(untitled) - Derryberry, Mayhew (San Francisco, 2004)
Derryberry's Educating for Health includes the complete original text of his classic book with new chapters by current experts and teachers inthe field of health education and promotion. The book is organized into six sections: Linking Statistical Methods to Health Education, Education As a Challenge to All Health Professions, Establishing the Parameters of Health Education, Community Health Education, Influencing the International Health Field, and Research in Public Health Issues.
Keywords: Health education,Public health,Research,Giáo dục sức khỏe; Collected Works,Collected Works,Methods,Phương pháp